The surveillance of viral infections by the unconventional Type I NKT cell - Rajashekar, Varshini; Stern, Lauren; Almeida, Catarina F.; Slobedman, Barry; Abendroth, Allison (Frontiers in Immunology, 2024)
Type I NKT cells, also known as Invariant Natural Killer T (iNKT) cells, are a subpopulation of unconventional, innate-like T (ILT) cells which can proficiently influence downstream immune effector functions. Type I NKT cells express a semi-invariant ab T cell receptor (TCR) that recognises lipid-based ligands specifically presented by the nonclassical cluster of differentiation (CD1) protein d (CD1d) molecule. Due to their potent immunomodulatory functional capacity, type I NKT cells are being increasingly considered in prophylactic and therapeutic approaches towards various diseases, including as vaccine-adjuvants. As viruses do not encode lipid synthesis, it is surprising that many studies have shown that some viruses can directly impede type I NKT activation through downregulating CD1d expression. Therefore, in order to harness type I NKT cells for potential anti-viral therapeutic uses, it is critical that we fully appreciate how the CD1d-iNKT cell axis interacts with viral immunity. In this review, we examine clinical findings that underpin the importance of type I NKT cell function in viral infections. This review also explores how certain viruses employ immunoevasive mechanisms and directly encode functions to target CD1d expression and type I NKT cell function. Overall, we suggest that the CD1d-iNKT cell axis may hold greater gravity within viral infections than what was previously appreciated.